Portfolio planning and risk management in the pharmaceutical industry 2 - Greuel, Joachim M. (Henry Stewart Talks, 2017)
Portfolio planning and risk management, Added value per completed milestone, Portfolio: NPV distribution for various numbers of preclinical projects, Portfolio management: risk / return plot, Risk structure and value uptake of 3 R&D projects, Project and portfolio value maximization, Risk management perspectives, Risk of alternative development plans, Decision criteria beyond absolute value, Risk-adjusted NPV and productivity index, Portfolio productivity, Portfolio management implementation milestones